Are behaviour problems in extremely low‐birthweight children related to their motor ability?. (27th January 2017) - Danks, Marcella; Cherry, Kate; Burns, Yvonne R.; Gray, Peter H.
Abstract: Aim: To investigate whether behaviour problems are independently related to mild motor impairment in 11–13‐year‐old children born preterm with extremely low birthweight (ELBW). Methods: The cross‐sectional study included 48 (27 males) non‐disabled, otherwise healthy ELBW children (<1000 g) and 55 (28 males) term‐born peers. Parents reported behaviour using the Child Behaviour Checklist (CBCL). Children completed the Movement Assessment Battery for Children (Movement ABC). Results: Extremely low birthweight children had poorer behaviour scores (CBCL Total Problem T score: mean difference = 5.89, 95% confidence interval = 10.29, 1.49, p = 0.009) and Movement ABC Total Motor Impairment Scores (ELBW group median = 17.5, IQR = 12.3; term‐born group median = 7.5, IQR = 9, p < 0.01) than term‐born peers. Behaviour was related to motor score (regression coefficient 2.16; 95% confidence interval 0.34, 3.97, p = 0.02) independent of gender, socio‐economic factors or birthweight. Motor score had the strongest association with attention ( ρ = 0.51; p < 0.01) and social behaviours ( ρ = 0.50; p < 0.01). Conclusion: Behaviour problems of otherwise healthy 11‐ to 13‐year‐old ELBW children are not related to prematurity independent of their motor difficulties. Supporting improved motor competence in ELBW preteen children may support improved behaviour, particularly attention and social behaviours.